2013
DOI: 10.1016/j.neuron.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neuron Fates Are Distinguished by a Transcriptional Switch that Regulates Dendrite Branch Stabilization

Abstract: SUMMARY Sensory neurons adopt distinct morphologies and functional modalities to mediate responses to specific stimuli. Transcription factors and their downstream effectors orchestrate this outcome but are incompletely defined. Here, we show that different classes of mechanosensory neurons in C. elegans are distinguished by the combined action of the transcription factors MEC-3, AHR-1, and ZAG-1. Low levels of MEC-3 specify the elaborate branching pattern of PVD nociceptors, whereas high MEC-3 is correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
153
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(174 citation statements)
references
References 67 publications
(141 reference statements)
13
153
4
Order By: Relevance
“…Class--specific dendrite targeting is regulated via the activity of transmembrane adhesion proteins. For example, in C. elegans, class--specific expression patterns of the transcription factors MEC--3, AHR--1, and ZAG--1 regulate the morphology of mechanosensory neurons, and MEC--3 promotes differential expression of the Claudin--like membrane protein HPO--30 to enable lateral branch stabilization 10 .…”
mentioning
confidence: 99%
“…Class--specific dendrite targeting is regulated via the activity of transmembrane adhesion proteins. For example, in C. elegans, class--specific expression patterns of the transcription factors MEC--3, AHR--1, and ZAG--1 regulate the morphology of mechanosensory neurons, and MEC--3 promotes differential expression of the Claudin--like membrane protein HPO--30 to enable lateral branch stabilization 10 .…”
mentioning
confidence: 99%
“…Transcription factors may suppress alternative programs of differentiation and promote neuronal diversity by direct repression of other transcription factors, repression of their downstream target genes, or by competitive binding of common cofactors to block transcription factor function Borromeo et al, 2014;Gordon and Hobert, 2015). Differential expression levels of the same transcription factor can also drive distinct morphology, identity and connectivity to further increase diversity in the nervous system (Grueber et al, 2003;Chen et al, 2006;Dasen et al, 2008;Smith et al, 2013). It has been proposed that such transformations from one cell type, or cell characteristic, to another by mutations in terminal selector genes might provide a basis for the evolutionary diversification of cell types in the nervous system (Arlotta and Hobert, 2015).…”
Section: Transcriptional Control Of Cut Levelsmentioning
confidence: 99%
“…In mec-3 mutants, the PVD cell body position and axon are normal, but PVD dendrites display dramatic growth defects and fail to initiate secondary branches (Smith et al, 2010;Tsalik et al, 2003). These defects are rescued by PVD-specific expression of MEC-3 (Smith et al, 2013).…”
Section: Transcriptional Regulation Of Morphology In Drosophila Dendrmentioning
confidence: 99%
“…A recent study identified hpo-3/claudin as a downstream effector of MEC-3 in regulating PVD morphology (Smith et al, 2013). Miller and colleagues compared the mRNA profiles of PVD neurons from wild-type animals with those from mec-3 mutants and identified many putative MEC-3 targets, including hpo-30/ claudin.…”
Section: Transcriptional Regulation Of Morphology In Drosophila Dendrmentioning
confidence: 99%
See 1 more Smart Citation